A Descending Circuit Derived From the Superior Colliculus Modulates Vibrissal Movements - Kaneshige, Miki; Shibata, Ken-ichi; Matsubayashi, Jun; Mitani, Akira; Furuta, Takahiro (Frontiers in Neural Circuits, 2018)
The superior colliculus (SC) is an essential structure for the control of eye movements. In rodents, the SC is also considered to play an important role in whisking behavior, in which animals actively move their vibrissae (mechanosensors) to gather tactile information about the space around them during exploration. We investigated how the SC contributes to vibrissal movement control. We found that when the SC was unilaterally lesioned, the resting position of the vibrissae shifted backward on the side contralateral to the lesion. The unilateral SC lesion also induced an increase in the whisking amplitude on the contralateral side. To explore the anatomical basis for SC involvement in vibrissal movement control, we then quantitatively evaluated axonal projections from the SC to the brainstem using neuronal labeling with a virus vector. Neurons of the SC mainly sent axons to the contralateral side in the lower brainstem. We found that the facial nucleus received input directly from the SC, and that the descending projections from the SC also reached the intermediate reticular formation and pre-Bötzinger complex, which are both considered to contain neural oscillators generating rhythmic movements of the vibrissae. Together, these results indicate the existence of a neural circuit in which the SC modulates vibrissal movements mainly on the contralateral side, via direct connections to motoneurons, and via indirect connections including the central pattern generators.